Identification of the Notch ligand DLK1 as an immunotherapeutic target and regulator of tumor cell plasticity and chemoresistance in adrenocortical carcinoma - Nai-Yun Sun; Suresh Kumar; Yoo Sun Kim; Diana Varghese; Arnulfo Mendoza; Rosa Nguyen; Reona Okada; Karlyne Reilly; Brigitte Widemann; Yves Pommier; Fathi Elloumi; Anjali Dhall; et al. (Nature Communications)
Abstract While immunotherapeutic targeting of cell surface proteins is an increasingly effective cancer therapy, identification of new surface proteins, particularly those with biological importance, is critical. Here, we uncover delta-like non-canonical Notch ligand 1 (DLK1) as a cell surface protein with limited normal tissue expression and high expression in multiple refractory adult metastatic cancers including small cell lung cancer (SCLC) and adrenocortical carcinoma (ACC), a rare cancer with few effective therapies. In ACC, ADCT-701, a DLK1 targeting antibody-drug conjugate (ADC), shows in vitro and in vivo activity but is overall limited due to high expression and activity of the drug efflux protein ABCB1 (MDR1, P-glycoprotein). In contrast, ADCT-701 induces complete responses in DLK1+ ACC and SCLC in vivo models with low or no ABCB1 expression. Genetic deletion of DLK1 in ACC dramatically downregulates ABCB1 and increases ADC payload and chemotherapy sensitivity through NOTCH1-mediated transdifferentiation. This work identifies DLK1 as an immunotherapeutic target that regulates tumor cell plasticity and chemoresistance in ACC and supports an active phase I clinical trial targeting DLK1 with an ADC in ACC and neuroendocrine neoplasms (NCT06041516).